Constructing High‐Performance Quasi‐Solid‐State Sulfur Cathodes via the Cooperation of Solid Electrolyte Interface and Selenium Doping. Issue 10 (24th May 2022) - Wang, Xumin; Li, Shuping; Wu, Qiang; Sun, Mengjun; Yu, Chuang; Xie, Jia
Abstract: Sulfur cathodes with quasi‐solid‐state conversion can prevent the dissolution and diffusion of polysulfides, effectively avoiding the "shuttle effect". However, sulfur cathodes under quasi‐solid‐state conversion suffer from inferior electrochemical performance, due to unstable solid electrolyte interface (SEI) and intrinsically sluggish reaction kinetics. Herein, the cooperation of a robust SEI and eutectic accelerator Se is employed to improve the performance of quasi‐solid‐state sulfur cathodes. SEI is formed through the nucleophilic reaction in diluted concentrated electrolyte between limited soluble polysulfides/polyselenides and vinylene carbonate, which is robust and displays low SEI resistance. Se doping leads to smaller overpotential, lower charge transport resistance, and superior rate capability and cyclability. The Se doped sulfur cathode delivers a discharge capacity of 3.7 times than the pure sulfur cathode at 1 A g −1 and maintains a capacity retention of 99.4 % after 100 cycles. This work demonstrates an effective strategy to construct quasi‐solid‐state sulfur cathodes for high‐performance metal‐sulfur batteries. Abstract : The cooperation between a robust solid electrolyte interface (SEI) film and selenium doping is used to construct high‐performance quasi‐solid‐state conversion sulfur cathodes with excellent cyclability and rate capability. A robust SEI is formed by nucleophilic reaction between polysulfide and vinylene carbonate in a diluted concentrated electrolyte. Se‐doped sulfur cathode displays smaller overpotential and lower SEI resistance.